2018
DOI: 10.1016/j.dendro.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Dendrochronological assessment of British veteran sweet chestnut (Castanea sativa) trees: Successful cross-matching, and cross-dating with British and French oak (Quercus) chronologies

Abstract: Dendrochronological assessment of British veteran sweet chestnut (Castanea sativa) trees: successful cross-matching, and cross-dating with British and French oak (Quercus) chronologies Across Britain and continental Europe there are many ancient Castanea sativa trees of great significance for natural and cultural heritage, yet scant assessment has been made of them for dendrochronological information. This paper describes the dendrochronological analysis of 28 Castanea sativa trees (veteran historic trees, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Chestnut is characterized by relatively wide tree rings [4][5][6], and it is not a particularly sensitive species in terms of dendrochronology [35]. Moreover, is not studied much from the dendrochronological point of view [36], and physiological studies of the species are also quite rare [9,37,38]. Based on dendrometric parameters, the selected stands in our study were found to be quite different from each other, mainly in the number of stumps/ha and the number of stems/stumps.…”
Section: Species Signalsmentioning
confidence: 77%
“…Chestnut is characterized by relatively wide tree rings [4][5][6], and it is not a particularly sensitive species in terms of dendrochronology [35]. Moreover, is not studied much from the dendrochronological point of view [36], and physiological studies of the species are also quite rare [9,37,38]. Based on dendrometric parameters, the selected stands in our study were found to be quite different from each other, mainly in the number of stumps/ha and the number of stems/stumps.…”
Section: Species Signalsmentioning
confidence: 77%